Sustainable but hungry? Food security outcomes of certification for cocoa and oil palm smallholders in Ghana - Dompreh, E.B.; Asare, R.; Gasparatos, A. (IOP Publishing, 2021)
Cocoa and oil palm are the major commodity crops produced in Ghana and livelihood options for hundreds of thousands of rural households. However, their production has negative environmental and socioeconomic impacts. Certification standards have been promoted as a market-led mechanism to ensure their sustainable production. Even though food security does not feature in the theory of change of most certification standards, there are interesting intersections. This paper assesses the food security outcomes of certification adoption among cocoa and oil palm smallholders in Ghana. We analyse 608 household surveys from two study sites using propensity score matching and multiple standardized metrics of food security such as the Food Consumption Score (FCS), the Household Food Insecurity Access Scale (HFIAS) and the Coping Strategies Index. Certified cocoa/oil palm farmers are more food secure than uncertified farmers and food crop farmers across most indicators and group comparisons. However, the differences are for most indicators not substantial or statistically significant (except the HFIAS). In fact, 65% and 68% of the certified cocoa and oil palm farmers are vulnerable to food insecurity in terms of the FCS. These results suggest that even though certification adoption can improve the livelihoods and yields of farmers, in reality it has marginal effect on food security. Certification standards would need to emphasize food security in their guidelines, theories of change and support packages to smallholders if they are to enhance food security and have a truly positive effect on the sustainability of cocoa and oil palm production.